Metastatic melanoma causing small bowel perforation: A case report. (April 2023) - Pacilli, Mario; Gerundo, Alberto; Pavone, Giovanna; Fersini, Alberto; Ambrosi, Antonio; Tartaglia, Nicola
Abstract: Introduction and importance: Metastatic localization of melanoma often affects the gastrointestinal tract, with reference to the small intestine. Case presentation: In this work we present the clinical course of a patient affected by a surgically treated melanoma of the right conjunctiva, suddenly manifesting abdominal symptomatology. The abdominal computed tomography scan (CT scan) show evidence of free air into the peritoneal cavity, cholecystitis and brain lesions highly suspicious for metastases. Patient underwent emergency surgery, consisting of ileo-cecal resection, cholecystectomy, with the construction of an ileostomy. The histological examination diagnosed multiple ileal and gallbladder localizations of pigmented epithelial melanoma, and localization. Clinical discussion: The treatment of conjunctival melanoma consists in surgical removal. Distant metastases frequently affect the gastrointestinal tract, leading to the necessity to assess patients with abdominal symptoms, in order to avoid emergency scenarios such as the one reported in our study. Conclusions: Intra-abdominal metastases from melanoma are an event that should not be underestimated, because if detected in time, they can be treated with surgery resulting in a clear improvement in the prognosis. Late diagnosis of intestinal metastases can cause an acute abdomen scenario frequently caused by intestinal obstruction or gastrointestinal bleeding. Highlights: Metastatic localizations of melanoma often affect in the gastrointestinal tract. The small intestine is the most involved organ. Prognosis is poor in advanced disease with a median survival rate of approximately eight months Gastrointestinal dissemination of malignant melanoma should be assessed in patients with anaemia, intestinal occlusion, and other abdominal symptoms Locations to the gallbladder are rare, could mimic a scenario of cholecystitis Late diagnosis of intestinal metastases can cause an acute abdomen scenario frequently caused by intestinal obstruction or gastrointestinal bleeding.